Sistema de tratamento de efluentes sanitários na mina do Sossego, Canaã dos Carajás, Pará - MARQUES, Gabriela Cavalcante (2019)
This study aimed the evaluating both the efficiency and level of treatment of the effluents generated in a few compact treatment plants for sanitary effluents that were installed in the Sossego mine, Canaã dos Carajás, Pará state. These plants consist of railing box, watch box, septic tank, biofilter and chlorination box. All investigated plants were described, as well as the procedures of maintenance and operation of the decontamination system. From April to August, 2013, these plants, subjected to biological treatment (anaerobic micro-organisms), were monitored and showed efficiencies greater than 60 % which meet the current legislation as far as the waste disposal in the surrounding environment is concerned. As such, the Sossego mining activity conforms to the environmental sustainability precepts.